Oncolytic parvovirus H1 induces release of heat-shock protein HSP72 in susceptible human tumor cells but may not affect primary immune cells - Möhler, Markus; Rommelaere, Jean (Cancer gene therapy, 2003)
Certain autonomous parvoviruses preferentially replicate in and kill in vitro-transformed cells and may reduce the incidence of spontaneous and implanted tumors in animals. Hence, these viruses and their derivatives are currently under evaluation as antitumor vectors. However, the mechanisms underlying their tumor-suppressing properties are not yet understood. We asked whether the lytic parvovirus H1 may enhance the immunogenicity of infected tumor cells. Out of human melanoma and gastrointestinal tumor cells, we selected the cell line SK29-Mel-1 being very susceptible to H1-induced apoptotic killing. Here, no upregulation of HLA class I and costimulatory molecules could be observed following H1 infection. However, a strong release of the immunogenic signal—the inducible heat-shock protein HSP72, but not constitutive HSP73—was observed after H1 infection. The HSP72 release was higher and of longer duration than a conventional heat-shock treatment. We also explored H1 replication and cytotoxicity in human immune cells, as such cells may constitute targets for H1 virus replication. Long-term cultured lymphocytes, monocytes, immature and mature dendritic cells were not susceptible to H1 virus. Altogether, parvovirus-mediated cell killing may in vivo enhance tumor immunogenicity by HSP72 release and thus contribute to the antitumor effect of parvoviruses.